Ferbat's test: A Monte Carlo multiple comparison procedure with a control - Batista, Ben Dêivide de Oliveira; Ferreira, Daniel Furtado (Brazilian Journal of Biometrics, 2024)
The present work presented an alternative MCC to the Dunnett's test, called Ferbat's test. The test replaced the root of the mean square of the residue used within Dunnett's test with another non-biased $σ$ estimator. The distribution of the test statistics was determined by simulation using the Monte Carlo method. Comparing the performance evaluation of these two tests, the Ferbat's test performed better in some scenarios, such as control of the experimentwise error rate for all simulated situations and higher power when the number of treatments was small and when the number of replications increases. In the other evaluation situations, the tests presented equivalent performance.